Specific gut microbiota may increase the risk of erectile dysfunction: a two-sample Mendelian randomization study - Su, Quanxin; Long, Yanxi; Luo, Yayin; Jiang, Tao; Zheng, Lei; Wang, Kenan; Tang, Qizhen (Frontiers in Endocrinology, 2023)
Objective: Studies have found that gut microbiota may be associated with the development of erectile dysfunction (ED); however, the exact link between the two remains unclear. This study aimed to elucidate the relationship between the gut microbiota and the risk of ED from a genetic perspective.We investigated the relationship between the gut microflora and ED using two-sample Mendelian randomization. GWAS-pooled data for ED were obtained from 223805 participants in Europe. GWAS summary data for ED were obtained from 223805 subjects in Europe and that for the gut microbiota were obtained from 18340 participants in 24 cohorts. We used the inverse-variance weighted (IVW) estimator as the primary method for the preliminary analysis, and the MR-Egger, weighted median (WM), simple model, and weighted model as secondary methods. We used Cochrane's Q-test, to detect heterogeneity, MREgger to detect pleiotropy, and the leave-one-out method to test the stability of the MR results. Ultimately, we genetically predicted a causal relationship between 211 gut microbiota and ED.Results: A total of 2818 SNPs associated with gut microflora were screened in the ED correlation analysis based on the assumption of instrumental variables. The results of MR analysis showed a causal relationship between the six gut microbes and ED occurrence. The results of the fixed effects IVW method revealed five gut microflora, including Lachnospiraceae (OR, 1.265; P = 0.008), Lachnospiraceae NC2004 group (OR, 1.188; P = 0.019), Oscillibacter (OR, 1.200; P = 0.015), Senegalimassilia (OR, 1.355; P = 0.002), Tyzzerella3 (OR, 1.133; P = 0.022), to be negatively associated with ED. In addition, the IVW method revealed Ruminococcaceae UCG-013 (OR, 0.827; P = 0.049) to be positively associated with ED. Quality control results showed no heterogeneity or horizontal pleiotropy in the MR analysis (P > 0.05).Conclusions: Six gut microbes were genetically associated with ED; of which, Ruminococcaceae UCG-013 was causally associated with a reduced risk of ED development. Our findings provide a new direction for research on the prevention and treatment of ED; however, the mechanisms and details require further investigation.